2010
DOI: 10.1007/s10620-009-1091-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of H. Pylori on Growth: Is the Infection or Mucosal Disease Related to Growth Impairment?

Abstract: Recurrent abdominal pain associated with gastric mucosal injury plays a role in a decrease in BMI independent of H. pylori infection. However, if recurrent abdominal pain originates from H. pylori infection, it appears that linear growth is also affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
(38 reference statements)
1
28
0
1
Order By: Relevance
“…Because of this, FEV 1 is height dependent 14. In the present study, the mean difference in height between the seropositive and seronegative individuals was 0.012 m. Our data are in keeping with a large body of literature demonstrating that chronic infection with this bacterium impairs growth during childhood, which manifests as shorter adult height 15 16. One study found that the average difference in height between H. pylori positive and negative individuals was 0.035 m 16.…”
Section: Discussionsupporting
confidence: 89%
“…Because of this, FEV 1 is height dependent 14. In the present study, the mean difference in height between the seropositive and seronegative individuals was 0.012 m. Our data are in keeping with a large body of literature demonstrating that chronic infection with this bacterium impairs growth during childhood, which manifests as shorter adult height 15 16. One study found that the average difference in height between H. pylori positive and negative individuals was 0.035 m 16.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in adults, HP eradication has been shown to be followed by weight gain [19, 37]. In contrast, some reports have indicated that HP-related gastric symptoms, not HP infection itself, induce malnutrition [16, 38]. While the effect of this phenomenon on our conclusions cannot be quantified at the moment, our observation that low HP infection, and not negative HP infection status, is associated with the lowest risk of MetS might be explained by the inverse effect of HP infection and associated gastric symptoms on overnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…An apparent negative impact of H. pylori infection on growth velocity or height has been documented in cohort studies in infants 6,7,8 and school age children 9 , as well in several well designed cross-sectional studies 10,11,12 . Although the amount and quality of the evidence seems to support the association of H. pylori infection and growth, it is not known whether attained height and weight in children will be impacted over the long term.…”
Section: Introductionmentioning
confidence: 90%